Early Permian high-K calc-alkaline volcanic rocks from NW Inner Mongolia, North China: geochemistry, origin and tectonic implications - Zhang, Xiao-hui; Wilde, Simon; Zhang, H.; Zhai, M. (Geological Society Publishing House, 2011)
Knowledge of the characteristics of the extensive late Palaeozoic volcanic rocks across the northernChina–Mongolia tract is essential for understanding the tectonic evolution and continental crustal growth in the Central Asian Orogenic Belt. This geochronological and geochemical study documents the Early Permian mafic and felsic volcanic rocks from northwestern Inner Mongolia. The mafic rocks form two magma series with distinctive geochemical characteristics; one showing large ion lithophile element (LILE) enrichment relative to high field strength elements (HFSE) and an asthenosphere-like Sr–Nd–Pb isotopic signature, and the other featuring an elevated Nb and lithospheric isotopic signature. This result indicates that two mantle source components are involved in the magma generation: the subduction-related metasomatized asthenosphere and lithospheric mantle. The felsic rocks show strong enrichment of LILE and light REE, depletion in HFSE, and indistinguishable isotopic compositions from mafic ones. Such features are consistent with partial melts of mixed sources composed of predominant juvenile basaltic underplates and minor ancient crustal materials. These mafic and felsic rocks constitute a post-subduction high-potassium calc-alkaline magmatic suite possibly under a geodynamic regime of Palaeo-Asian Ocean slab breakoff. This regime not only provides a feasible trigger for the flipping of subduction polarity in the Solonker suture zone, but also presents a favourable venue for vertical continental crustal growth.